2009
DOI: 10.1111/j.1440-1819.2009.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Better efficacy for the osmotic release oral system methylphenidate among poor adherents to immediate‐release methylphenidate in the three ADHD subtypes

Abstract: Aims:To determine factors for switching to osmotic release oral system methylphenidate (OROS-MPH) among poor adherents to immediate-release methylphenidate (IR-MPH); and to compare the efficacy of OROS-MPH on the three attention-deficit/ hyperactivity disorder (ADHD) subtypes in a multisite prospective observational study in Taiwan. Methods:The sample included 240 children with ADHD, aged 6-16 years, who were poor adherents to IR-MPH, 137 of whom were switched to OROS-MPH. The child psychiatrists diagnosed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Similar to the results in Western countries, the efficacy and safety of IR-MPH and OROS-MPH have been established in two clinical trials conducted in ethnic Chinese ADHD populations (Yang et al 2004;Gau et al 2006). In addition, after switching to OROS-MPH from IR-MPH, the improvement in remission rates of ADHD, behaviors, and school performance through improving patients' drug adherence have been demonstrated in two multisite studies conducted among Chinese ADHD populations in Taiwan (Gau et al, 2008a;Chou et al, 2009).…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Similar to the results in Western countries, the efficacy and safety of IR-MPH and OROS-MPH have been established in two clinical trials conducted in ethnic Chinese ADHD populations (Yang et al 2004;Gau et al 2006). In addition, after switching to OROS-MPH from IR-MPH, the improvement in remission rates of ADHD, behaviors, and school performance through improving patients' drug adherence have been demonstrated in two multisite studies conducted among Chinese ADHD populations in Taiwan (Gau et al, 2008a;Chou et al, 2009).…”
Section: Introductionsupporting
confidence: 56%
“…Our study showed that at the baseline, the mean IR-MPH daily dose after at least 1 month of treatment was only 21.4 mg (0.61 mg/kg) and the remission rate at the baseline prior to the switch to OROS-MPH was only 4.9%. This finding suggests that even with the use of rating scales, child psychiatrists tend to use relatively low doses of drugs, such as IR-MPH twice a day, because of their concern about side effects and the patient's intolerance of medications, even though the patients still exhibit symptoms (Chou et al 2009). Therefore, we can see that the clinical practice in Taiwan is relatively conservative, in which drugs given to ADHD children and adolescents are initially prescribed at a low level and are slowly titrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 26 items of the SNAP-IV are rated on a four point Likert scale, with scores of 0-3 representing ''not at all,'' ''just a little,'' ''quite a bit,'' and ''very much,'' respectively. The Chinese SNAP-IV-Parent (Gau et al 2008) and -Teacher ) Forms have good validity and reliability, and have been widely used in clinical trials to assess the efficacy of OROS-methylphenidate (Chou et al 2009) and atomoxetine (Gau and Shang 2010) in children with ADHD.…”
Section: Secondary Efficacy Measuresmentioning
confidence: 99%
“…Note that the above studies were mostly conducted with immediate release stimulants; an important but less well-studied factor is whether adherence varies as a function of the formulation used (i.e., immediate-release or extendedrelease). This evolving literature suggests that adherence is somewhat improved with extended-release versus immediate-release forms of medication [22,27,32], although extended-release forms of stimulant medication do not always result in greater adherence over extended periods of time [33].…”
Section: Adherence In Youth With Adhdmentioning
confidence: 99%